In the shadow of the capitol dome : critical legal theory and state level educational policymaking - Boggs, Brian (Contemporary perspectives on educational politics and the law, 2024)
"The Tenth Amendment of the United States Constitution places education firmly under the purview of the states. As such, and from the time the first public education system was conceived in the United States, there have been endless battles under the domes of state capitals everywhere to create, control, and reform educational policy. However, despite the prominent role that states and their legislatures have as central actors in forming educational policy, very few policy actors and even fewer academics have been able to pierce the veil of policymaking at the state level. This case study addresses that gap by examining how one particular educational policy - The Michigan Public Education Finance Act - was created, lived, died, and was resurrected in the State of Michigan. Through the exploration of this policy, there is a particular focus on the use of critical legal theory to examine hidden power structure embedded in the legislative legal system and apply this often-overlooked critical approach to education policy research. Readers will come to understand what educational policymaking looks like at the state level and how to engage their voice in the process. With the increasing political nature of education policy and the fight to control it in the halls of local state capitals, educators as well as the public need to know how to access the political system and have their voice heard. However, it can also appear to be impenetrable to an outsider. This book will demystify the policy making process"--